Short-term changes in added sugar consumption by adolescents reflected in the carbon isotope ratio of fingerstick blood. Issue 4 (December 2018) - Liu, Sarah V; Moore, Lori B; Halliday, Tanya M; Jahren, A Hope; Savla, Jyoti; Hedrick, Valisa E; Marinik, Elaina L; Davy, Brenda M
Background: Consumption of added sugars (AS) and sugar-sweetened beverages (SSB) may adversely affect adolescents' weight and cardiovascular disease risk. Reliance on self-reported dietary assessment methods is a common research limitation, which could be overcome by dietary intake biomarkers. Aim: The investigation was a proof-of-concept study to evaluate the proposed carbon isotope ratio (δ 13 C) biomarker of AS intake in adolescents, using a controlled feeding design. Methods: Participants ( n = 33, age 15.3 years, 53% female) underwent two seven-day controlled feeding periods in a randomly assigned order. Diets were matched in composition except for AS content (5% or 25% of total energy). Fasting fingerstick blood samples were collected daily during each diet period. Results: Fingerstick δ 13 C values changed from day 1 to 8 by –0.05 ± 0.071‰ on 5% AS, and +0.03 ± 0.083‰ on 25% AS ( p ≤ 0.001). Reliability was demonstrated between day 7 and 8 δ 13 C values on the 5% (ICC = 0.996, p ≤ 0.001) and 25% (ICC = 0.997, p ≤ 0.001) AS diets. Conclusions: Larger scale investigations are warranted to determine if this technique could be applied to population-level research in order to help assess the effectiveness of interventions aimed at reducing the consumption of AS or SSB intake.